The Long-term Evaluation Method of MBR Membrane - Li Dong; Zhang Xuemei; Ma Qinghua; Fu Bo; Qin Baolan; Hao Jingyuan (Current Approaches in Engineering Research and Technology Vol. 2, 2024)
The permeable volume and trans-membrane pressure difference of all 3520 days, from October 2011 to November 2021, in an A2/O-MBR RWTP (recycled water treatment plant) in Xi’an Siyuan University have been indiscriminately used to study an evaluation method of MBR hollow fiber membrane. The 1 m3permeable volume of 1000 m2membrane area at 1 day and 1 kPa trans-membrane pressure (TMP) difference is defined as one industrial permeability, 1 VMD. The VMD of every day is directly calculated by using the daily computer’s records of the RWTP. After excluding some anomalies from the original data, an arithmetic average of each 25 days (as a group unit) effective VMD was calculated. Then, group units are reduced into annual units. After four years, a power equation is fitted into the annual VMD attenuation equation of the previous four years of RWTP operation. The calculation of the annual VMD attenuation equation is straightforward, simple, and convenient. The VMD declined annually by about 0.78. The TMP increased annually by about 0.66 kPa.